Assessing Internet Addiction Levels Among Medical Students in Jordan_ Insights from a Cross-Sectional Survey - Mutaz Abdel Wahed; Salma Abdel Wahed (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
This Study designed to explore internet addiction among medical students in Jordan, associated factors of internet addiction, possible effects on academic performance and possible interventions. A cross-sectionals study was performed with 172 medical students from different Jordanian university, aged 18-23 years. Internet Addiction Test (IAT) created by Dr. Kimberly Young was used to assess addiction level. The results showed that 43% of the students had medium internet addiction. These students mostly used social media activities for three to six hours daily. The study also revealed that male' students had much more sever addiction than females. In addition, males had higher rate of medium internet addiction. Excessive use of the internet was inversely proportional to academic proportional to academic performance and sleep patterns according to previous studies as mentioned. Suggested solutions included controlled internet bundle, parental involvement, pharmacological and non-pharmacological treatments. The study emphasizes to find proper strategies to prevent internet addiction among medical students and stands firm on early interventions to stop the negative consequences.